2020
DOI: 10.3389/fphys.2020.00434
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Peptide Hormones in Insect Lipid Metabolism

Abstract: Lipids are the primary storage molecules and an essential source of energy in insects during reproduction, prolonged periods of flight, starvation, and diapause. The coordination center for insect lipid metabolism is the fat body, which is analogous to the vertebrate adipose tissue and liver. The fat body is primarily composed of adipocytes, which accumulate triacylglycerols in intracellular lipid droplets. Genomics and proteomics, together with functional analyses, such as RNA interference and CRISPR/Cas9-tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(85 citation statements)
references
References 375 publications
(700 reference statements)
0
75
0
Order By: Relevance
“…Cytokines are a vast group of evolutionarily conserved peptide hormones that affect several biological processes, including inflammation and immunity [41,169]. Similarly to humans, insect cytokines are the major players in the coordination between the different components of the immune system [169].…”
Section: Cytokinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytokines are a vast group of evolutionarily conserved peptide hormones that affect several biological processes, including inflammation and immunity [41,169]. Similarly to humans, insect cytokines are the major players in the coordination between the different components of the immune system [169].…”
Section: Cytokinesmentioning
confidence: 99%
“…Tachykinins (TKs) are ancient widespread neuropeptides of which the best characterized to date is the vertebrate substance P, known to be involved for example in inflammation, immune responses, gut function and haematopoiesis [186]. In D. melanogaster, TKs were shown to be produced in enteroendocrine cells of the midgut and have been implicated in several aspects of metabolic stress regulation and hormone release [41,187,188]. More recently, it was also demonstrated that activation of the Imd pathway in the midgut leads to the expression and release of TK, which ultimately results in reduced IIS and lipid storage [189].…”
Section: Tachykininsmentioning
confidence: 99%
“…Nevertheless, when starvation was prolonged, the UCP5KO flies depleted their reserves more rapidly and died faster than controls [ 142 ]. Consistently with these findings, and considering that ectopic neuronal Dm UCP5 expression was able restore starvation resistance in UCP5KO flies, this carrier could be involved in the control of metabolic homeostasis at the brain level, by uncoupling mitochondria in brain neurosecretory cells and affecting their secretion of adipokinetic hormone (the fruit fly equivalent of glucagone) and insulin-like peptides [ 143 ]. In this light, Dm UCP5 could interfere with hormonal metabolic homeostasis, as observed for mammalian UCP2 [ 103 , 104 ].…”
Section: Drosophila Melanogaster Vs Human Mitomentioning
confidence: 67%
“…LdCrT and LdCnX expression was unaffected or downregulated in the fat body by post‐diapause, a phase requiring energy supply and lipolytic activity (Lehmann et al, 2016; May, 1989; Sinclair & Marshall, 2018; Toprak et al, 2014). As was also discussed in the context of starvation, fat body‐specific downregulation of both genes by post‐diapause might lead to a reduction in ER Ca 2+ levels (Brandt et al, 2019; W. A. Wang et al, 2017) and hydrolysis of lipids in adipocytes (Baumbach et al, 2014; Subramanian et al, 2013; Toprak, 2020), therefore, contributing to the supply of energy required for emergence from diapause. However, the fat body is not a primary site of expression for either gene in adults.…”
Section: Discussionmentioning
confidence: 97%
“…As was also discussed in the context of starvation, fat body-specific downregulation of both genes by post-diapause might lead to a reduction in ER Ca 2+ levels (Brandt et al, 2019;W. A. Wang et al, 2017) and hydrolysis of lipids in adipocytes (Baumbach et al, 2014;Subramanian et al, 2013;Toprak, 2020), therefore, contributing to the supply of energy required for emergence from diapause. However, the fat body is not a primary site of expression for either gene in adults.…”
Section: Diapause-related Expression Of Ca 2+ -Binding Chaperone Genesmentioning
confidence: 89%